Meningkatkan Kinerja Guru Madrasah Melalui Motivasi Kerja, Kepuasan Kerja, dan Komitmen Organisasi - Nur Aminatul Asma (Magister Teknologi Pendidikan Fakultas Ilmu Pendidikan Universitas Pelita Harapan, 2022)
Qualified teachers are one of the key factors determining school performance. High teacher performance can drive a school’s success. The purpose of this study is to analyze the influence of work motivation, job satisfaction, and organizational commitment on the performance of Madrasah teachers in Central Java. Data collection was conducted through a survey by distributing questionnaires to thirty one teachers. The data obtained were then analyzed using the PLS-SEM method to determine the path coefficients and hypothesis testing results. The findings of this study indicate that work motivation, job satisfaction, and organizational commitment have a positive influence on the performance of teachers at Madrasah XYZ, Bangsri, Jepara.